If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 + x + 2 = 2x + 20 Reorder the terms: 10 + 2 + 3x + x = 2x + 20 Combine like terms: 10 + 2 = 12 12 + 3x + x = 2x + 20 Combine like terms: 3x + x = 4x 12 + 4x = 2x + 20 Reorder the terms: 12 + 4x = 20 + 2x Solving 12 + 4x = 20 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 4x + -2x = 20 + 2x + -2x Combine like terms: 4x + -2x = 2x 12 + 2x = 20 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 2x = 20 + 0 12 + 2x = 20 Add '-12' to each side of the equation. 12 + -12 + 2x = 20 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 20 + -12 2x = 20 + -12 Combine like terms: 20 + -12 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| -3x+7=28 | | 3x-45=6 | | 7(n+6)+8(n+4)= | | 8(x+3)+14(x+2)=74 | | 3(6z-1)-4(z+9)=4(z+1) | | 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 | | 5b*6b= | | 3x*5x*2x= | | 6(2z-1)-2(z+3)=3(z+1) | | 20y-10=10 | | 3a*4a= | | b/14=5/10 | | X+(-4)+2x=14 | | 9-10x=77-38x | | -18x^2+65x+7=0 | | 3x^3-7x^2=-10 | | 9d-2d+6d-6=6d | | y/8=2/10 | | (3+5x^2)(3-5x^2)= | | 3x^3-7x^2=10 | | 9x-7=6x+16 | | (2x+3)2-3x-4=0 | | 16a^3b+4ab=0 | | 6+9+6= | | 12X^3+3X^2-24X^2-6X=0 | | (x+2)(x+8)=72 | | 5s+12=0 | | (3d^4-4d^3+6)(-3c^2d)= | | 12X^3+3X^2-24X-6X=0 | | -x^2+5x=3 |